Aymara customs and rites in the rural area of ​​Achacachi (Bolivia) - Allen, Guillermo (1972)
The family joys of the laymara are naturally centered in their home. At home he is alone with his wife and children, away from other relatives. There you can share everything with your wife. His ancestral obligations continue to bind him to the community, but within the domestic walls the Aymara is temporarily detached from them and can postpone them for a few hours. For all of them, the planning and construction of a new house, to house a new existence within its walls, is an occasion for communal work and recreation.